Hydrological River Regime and Sedimentation on the Large Siberian Rivers During the Last 100 000 Years - DOI 10.5216/bgg.v19i1.15337 - A, Yamskikh; G, Yamskikh; A.A, Yamskikh (Boletim Goiano de Geografia, 2011)
.